A profile of chromosome counts, male meiosis and pollen fertility in 45 species of Asteraceae from Parvati Valley in Kullu district, Himachal Pradesh. Issue 2 (3rd April 2017) - Gupta, Himshikha; Gupta, Raghbir Chand; Kumar, Rohit; Singhal, Vijay Kumar
Abstract: Chromosome counts including male meiotic studies have been made on 45 species (125 accessions) of Asteraceae collected from the Parvati Valley, Kullu district, Himachal Pradesh. Crepis foetida ( n = 5) and Senecio pedunculatus ( n = 20) have been counted chromosomally for the first time at global level. The genus Phagnalon has been worked out for the first time from India ( P. niveum, n = 9). New chromosome counts/cytotypes have been reported for Gerbera lanuginosa (2 n = 4 x = 48), Gynura cusimbua (2 n = 2 x = 16) and Inula grandiflora (2 n = 4 x = 32). Intraspecific euploid cytotypes have been reported for the first time in Inula grandiflora (2 x, 4 x ) . Three intraspecific euploid cytotypes (2 x, 3 x, 4 x ) have been reported from the valley in Taraxacum officinale complex. The triploid taxa re-recorded presently for Erigeron annuus (2 n = 27), Eupatorium adenophorum (2 n = 51) and Taraxacum officinale (2 n = 24) exhibit abnormal meiotic course and high pollen sterility but seem to have reproduced successfully through apomictic means. Presence of multivalents in the 4 x cytotype of Chrysanthemum leucanthemum (2 n = 36) indicates the segmental allotetraploid nature of the taxon. Phenomenon of cytomixis involving chromatin transfer among neighboring meiocytes and associated meiotic irregularities have been detected in Artemisia maritima ( n = 9), Aster peduncularis ( n = 27), Crepis foetida ( n = 5), Erigeron annuus (2 n = 27), Inula grandiflora ( n = 8), Lactuca dolichophylla ( n = 8), Prenanthes brunoniana ( n = 8), Senecio graciliflorus ( n = 20) and S. rufinervis ( n = 20). In the rest of the species, the present findings substantiate earlier chromosome reports from other parts of Himalayas in India.